KECERNAAN PAKAN BERBENTUK PELET MENGANDUNG KULIT PISANG RAJA FERMENTASI DENGAN MIKROORGANISME LOKAL DIBANDINGKAN DENGAN Trichoderma harzianum PADA KELINCI REX JANTAN LEPAS SAPIH - julius ginting (Universitas Sumatera Utara, 2014)
ABSTRACT JULIUS SYAH PUTRA GINTING, 2014. “Feed digestibility of pellets containing banana peel fermentation with Local Microorganism and Trichoderma harzianum on weaning male rex rabbit. Under supervised by TRI HESTI WAHYUNI and ARMYN HAKIM DAULAY. The objective of research was to determine the effect of utilization fermented raja banana peel in rations of weaning males rex rabbit. The research had been conducted in the Laboratory of Animal Biology, Animal Husbandry Study Program, University of Sumatera Utara, started from August until November 2013. This research used 21 Rex rabbit, with initial body weights 732±66,74 g/head. The design experiment used completely randomized design with 7 treatments and 3 replications. The treatments consisted of ration P0 (complete feed Raja banana peel without fermentation 45%), P1 – P3 (complete feed Raja banana peel fermented by MOL P1: 15%, P2: 30%, P3: 45% ), and P4 – P6 (complete feed Raja banana peel fermented by Trichoderma harzianum P4: 15%, P5: 30%, P6: 45%). The results showed the average dry matter (DM) digestibility (%) for treatments P0, P1, P2, P3, P4, P5, and P6 were 60,81; 61,6; 62,68; 60,35; 59,09; 58,14; and 57,31 respectively, while for organic matter (OM) digestibility (%) 66,69; 66,71; 68,89; 66,17; 63,83; 63,70; and 63,63, respectively. Treatment P2 show higher than other treatment on DM and OM digestibility (P<0,05). It is conclude that fermented Raja banana peel by MOL can be used until level 30% in ration of weaning male rex rabbit. Keywords: Raja banana peel; MOL, Trichoderma harzianum fermentation; Weaning male Rex rabbit.